Use of acellular pertussis vaccines in the United States: can we do better? - Nicola P. Klein; Ousseny Zerbo (Taylor & Francis Group, 2017)
Introduction: Despite robust vaccination schedules and high vaccination rates, many countries, including the U.S., have seen large pertussis outbreaks with a shift in recent years in the distribution of disease burden towards adolescents and young adults. Areas covered: This perspective covers problems related to the increased incidence of pertussis among adolescents. Because the Tdap vaccine only protects against pertussis for 1-2 years after vaccination, we propose a new strategy which aims to optimize the benefit of Tdap in adolescents. Expert commentary: Current pertussis vaccination schedules are based on age and have not been effective at protecting adolescents and teenagers from pertussis outbreaks. An alternative to the current practice would be to take advantage of the cyclical nature of pertussis outbreaks. Rather than immunizing children and adolescent solely based on age regardless of risk of pertussis at that moment, perhaps we should consider a 'timed' Tdap. The goal would be to administer Tdap to susceptible adolescents and young adults during periods when there is a greater risk of being exposed to pertussis. This approach would optimize the use of an effective, but short-lived vaccine by maximizing protection at the time of increased risk.